Implementation of Group Discussion Method to Improve Students' Understanding of Islamic Education Learning at MTs Terpadu Darul Qudwah - Al Asady, Siti Masyruroh; Wasminingsih (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to determine the improvement of students' understanding of the material of Commendable Morals through the application of the group discussion method at the Darul Qudwah Integrated MTs. This type of research is Class Action Research (PTK) which is carried out in two cycles, where each cycle consists of planning, implementation, observation, and reflection stages. The subjects of the study were 32 students in grade VIII of MTs Terpadu Darul Qudwah, consisting of 15 male students and 17 female students. Data collection techniques use observation, tests, and documentation. Data analysis was carried out with qualitative and quantitative descriptive approaches to see the improvement in learning outcomes and student activity during the learning process. The results of the study showed a significant increase in students' understanding of the material of Commendable Morals after the application of the group discussion method. In the pre-cycle, student learning completeness only reached 46.9%, increasing to 71.9% in cycle I, and reaching 90.6% in cycle II. In addition, students' activeness in the learning process has also increased, as seen from participation in discussions and the ability to express opinions more confidently. Thus, it can be concluded that the application of the group discussion method is effective in increasing students' understanding and participation in the material of Commendable Morals at the Darul Qudwah Integrated MTs.